Exploring University Instructors’ Achievement Goals and Discrete Emotions - Rinas, Raven; Dresel, Markus; Hein, Julia; Janke, Stefan; Dickhäuser, Oliver; Daumiller, Martin (Frontiers in Psychology, 2020)
Emerging empirical evidence indicates that discrete emotions are associated with teaching practices and professional experiences of university instructors. However, further investigations are necessary given that university instructors often face high job demands and compromised well-being. Achievement goals, which frame achievement-related thoughts and actions, have been found to describe motivational differences in university instructors and are hypothesized to be associated with their discrete emotions. Moreover, as variation exists in how university instructors respond to job demands regarding their emotional experiences, certain goals may moderate this relationship on the basis of framing different interpretations and reactions to stressors. To investigate these links, 439 instructors (46.7% female) from German and Austrian universities completed a survey assessing their achievement goals, discrete emotions (enjoyment, pride, anger, anxiety, shame, and boredom), and job demands. As hypothesized, multiple regression analyses revealed that achievement goals were differentially and meaningfully associated with discrete emotions. Specifically, learning approach goals were positively related to enjoyment and negatively related to anger and boredom, while learning avoidance goals were positively related to anger. Performance (appearance) approach goals were positively related to pride, and performance (appearance) avoidance goals were positively related to anxiety and shame. Lastly, relational goals were positively related to shame and boredom, and work avoidance goals were negatively related to enjoyment and positively related to shame and boredom. Conclusive moderation effects on the relations between job demands and emotions were not found. Future research avenues aimed at further understanding the supportive role that achievement goals can have for university instructors’ emotional experiences and well-being are discussed.